2015
DOI: 10.1039/c5ra06529a
|View full text |Cite
|
Sign up to set email alerts
|

Highly flexible and transparent film heaters based on polyimide films embedded with silver nanowires

Abstract: Highly flexible AgNW/PI transparent film heaters with superior mechanical and thermal response behavior were fabricated using an all solution-coating method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 36 publications
1
74
0
Order By: Relevance
“…In this study, we use the latter technique that allows to fabricate large‐area transparent heaters. So far, transparent, flexible, stretchable, and even inkjet printed thin‐film heaters based on AgNWs and AgNW‐nanocomposites were studied in terms of transient thermal response, infrared properties, spatial heat distribution as well as for different carrier substrates such as poly(ethylene terephthalate) (PET), poly(ethylene naphthalate) (PEN), polyimide (PI), and glass .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we use the latter technique that allows to fabricate large‐area transparent heaters. So far, transparent, flexible, stretchable, and even inkjet printed thin‐film heaters based on AgNWs and AgNW‐nanocomposites were studied in terms of transient thermal response, infrared properties, spatial heat distribution as well as for different carrier substrates such as poly(ethylene terephthalate) (PET), poly(ethylene naphthalate) (PEN), polyimide (PI), and glass .…”
Section: Introductionmentioning
confidence: 99%
“…The nominal bending strain, ɛ, is defined as ɛ = d/R b , where d is the substrate thickness. 22 In the present case, ɛ is 0.01 for the CFH with T = 96%. The corresponding resistance change is expressed as ΔR s = (R s − R s0 )/ R s0 , where R s0 is the initial resistance and R s is the resistance after the bending test.…”
Section: Flexibility and Stretchabilitymentioning
confidence: 89%
“…Above all, the most critical issue is the limited power (P) that can be supplied to such materials. This severely restricts the maximum attainable temperature (T s ), since T s ∝ P. For example, the temperature ranges of graphene heaters, silver nanowire heaters, and heaters utilizing hybrid materials combining graphene and silver nanowires are 100-206°C, [19][20][21] 48-160°C, [22][23][24][25][26][27] and up to 225°C, 28,29 respectively.…”
Section: Introductionmentioning
confidence: 99%
“…QJ Huang reported AZO/AgNWs/AZO deposited onto polyimide films, which displays excellent thermostability and mechanical flexibility with the low surface roughness ( R -rms < 8 nm). Huang et al [16, 17] reported silver nanowires successfully embedded in polyimide films to prepare highly flexible and transparent film heaters.…”
Section: Introductionmentioning
confidence: 99%